Development of an experiment plan with 3D electrospinning equipment for cartilage tissue engineering - Amador, Rita Costa (2022)
One of the major challenges associated with tissue engineering cartilage is the difficulty to recreate the anisotropic organization of the fibers, in order to simulate the biomechanical properties of the native tissue. The main objective of this dissertation was the development and application of a plan of experiments with 3D electrospinning equipment for tissue engineering cartilage. This plan of experiments seeks to understand how the combination of different parameters associated with the used 3D electrospinning equipment, influences the characteristics and properties of the resulting scaffolds. In this dissertation, in an initial phase, a description of cartilage is presented in terms of its structure, function, and biomechanical properties. It was also carried out an evaluation of the biofabrication processes in tissue engineering, focusing on cartilage engineering and in particular in electrospinning processes with controlled fiber alignment. In another stage, the plan of experiments was established, with identification of the input variables and respective levels that were going to be controlled in the equipment, as well as the identification of the parameters that were analysed in the produced scaffolds, being that the input variables and the respective levels varied in function of the architecture of the scaffold. Three scaffolds architectures were selected from the development in previous works. The input variables of the electrospinning process that were associated with two levels were: the electrospun PCL flow rate, the deposition time in static alignment (line), the number of deposition cycles in angular rotation (mesh), the collector disks velocity and the total number of arcade alignment cycles. The analysed parameters in the produced scaffolds for different combination of input variables/levels were: the thickness, the weight, the three-dimensional organization of the scaffold, the fiber diameter, porosity, and the elastic modulus at compression for 10% deformation. An analysis of variance (ANOVA) was applied to determine the effects of the controlled input variables in the electrospinning process on the analysed parameters in the resulting scaffolds. In the results obtained for the three architectures of scaffolds, the flow rate variable presented statistical significance (p<0.05). The deposition time in static alignment (line) presented significance for some output parameters and in fuction of the architecture. For the number of deposition cycles in angular rotation (mesh) variable it showed significant effects for the generality of the output parameters in the second scaffold architecture. The number of total cycles in the third architecture had a statistical significance in the thickness and weight of the scaffold parameters, while the velocity of the collector disks presented significance for the thickness, fiber diameter and elastic modulus at compression parameters.